Arousal responses to added inspiratory resistance during REM and non-REM sleep in normal subjects. Issue 2 (February 1993) - Gugger, M; Bögershausen, S; Schäffler, L
Abstract : BACKGROUND: Arousal in response to increased airflow resistance during sleep, especially rapid eye movement sleep (REM), could be an important protective mechanism against asphyxia. METHODS: The arousal response to the application of an external inspiratory resistance of 25 cm H2O/l/s was determined during REM and non-REM sleep in ten healthy men. RESULTS: The number of arousals occurring within two minutes of the load application was significantly higher during REM sleep than during either of the non-REM sleep stages 2 and 3/4, and was similar to that during stage 1. The proportion of arousals to non-arousals decreased significantly from stage 1 to stage 4. The mean time to arousal in REM was significantly shorter than in non-REM stages 1, 2 or 3/4 and increased significantly from stage 1 to stage 3/4. The duration of sleep (comparing the results of the first with the second half of the sleep period time) did not modify the arousal response in stages 2 and 3/4. CONCLUSIONS: The results show a significantly increased arousal response to an added inspiratory resistive load in REM sleep compared with non-REM sleep stages 2, 3 or 4 in normal men. In the context of previous studies these data could add support to the hypothesis that the decreased arousal response during REM sleep in patients with sleep apnoea might be due to an impairment of the normal "central processing" of this stimulus.